Study of acupuncture for low back pain in recent 20 years: a bibliometric analysis via CiteSpace - Liang, Yu-Dan; Li, Ying; Zhao, Jian; Wang, Xiao-Yin; Zhu, Hui-Zheng; Chen, Xiu-Hua (Journal of pain research, 2017)
Acupuncture has been applied to relieve low back pain (LBP) in many countries. However, a bibliometric analysis of the global use of acupuncture for LBP is rare. The aim of this study was to demonstrate the state of the art and trends concerning the global use of acupuncture for LBP in recent 20 years. Literature relating to acupuncture for LBP from 1997 to 2016 was retrieved from Web of Science. CiteSpace was used to analyze country/institution, cited journals, authors/cited authors, cited references, and keywords. An analysis of counts and centrality was used to reveal publication outputs, countries/institutions, core journals, active authors, foundation references, hot topics, and frontiers. A total of 958 references were obtained, and the total number of publications continually increased over the investigated period. Journal articles (662) were the most frequently occurring document type. The most productive country and institution in this field was the USA (342) and Harvard University (47), respectively. The (69) was the most productive journal, and (636) was the most cocited journal, which reflected the nature of the research. The Haake's (2007) article (cocitation counts: 130) and the Cherkin's (2001) article (centrality: 0.59) were the most representative and symbolic references, with the highest cocitation number and centrality, respectively. Cherkin was the most influential author, with the highest number of publications of 25 and a cocitation number of 226. The four hot topics in acupuncture for LBP were research method, evaluation, economy, and comprehensive therapy. The three frontier topics were intervention, test reliability, and prevalence. This study provides an insight into acupuncture for LBP and valuable information for acupuncture researchers to identify new perspectives on potential collaborators and cooperative institutions, hot topics, and research frontiers.